Development of E-Module Elasticity Materials and Hooke's Law Using Flip PDF Corporate Edition to Improve Critical Thinking Ability of High School Students - Rita Erlina; Eko Risdianto; Dedy Hamdani (CV Media Inti Teknologi, 2022)
This study aims to determine the characteristics and feasibility of the e-module developed using flip pdf corporate edition to improve the critical thinking skills of high school students. This research is a follow-up research that has been done previously which is only limited to the analysis stage, the method in this research is R n D with the ADDIE model which has five stages, namely; analysis (analysis); design (design), development (development and testing); implementation (use); and evaluation (evaluation), but in this study it was only carried out until the develop stage. The assessment instrument used in this study was an expert validation sheet containing material aspects, language aspects and media aspects. Based on the results of product validation tests by experts, the percentage score of 88% for the material aspect, 92% for the language aspect, 89.58% for the media aspect, and 85% for the critical thinking aspect so that the total average score is 88.6% including the in the very valid category. And the result of student perception response showed very good with a percentage of 87.64 % . Thus, the e-module material on elasticity and Hooke's law uses a flip pdf corporate edition to improve the critical thinking skills of high school students into a product that is feasible to use.